A checklist of the soldier beetles (Coleoptera: Elateroidea: Cantharidae) of Iran - Fanti, Fabrizio; Ghahari, Hassan (Zootaxa, 2016)
The present paper is a collection of data and records taken from literature on the Cantharidae of Iran. New original records are also included. These data indicate that 12 genera and 84 species and subspecies of Cantharidae have been recorded from Iran. Fifteen of these species-level records require further data to confirm. Synonymies and distributional information, both general and local, are provided. Two genera: Macrocerus and Themus, and three species: Cordicantharis cordicollis (Küster, 1854), Themus glazunovi glazunovi (Barovskij, 1909) and Macrocerus oculatus Motschulsky, 1845, are reported as new country records for Iran.